HIF-1α: A Key Factor Mediating Tumor Cells from Digestive System to Evade NK Cell Killing via Activating Metalloproteinases to Hydrolyze MICA/B - Quan Zhu; Shuyi Tang; Ting Huang; Chunjing Chen; Biyuan Liu; Chuyu Xiao; Liugu Chen; Wang Wang; Fangguo Lu (Biomolecules)
Malignant tumors of the digestive system are widespread and pose a serious threat to humans. Immune escape is an important factor promoting the deterioration of malignant tumors in the digestive system. Natural killer cells (NK cells) are key members of the anti-tumor and immune surveillance system, mainly exerting cytotoxic effects by binding to the activating receptor natural killer cell group 2D (NKG2D) on their cell surface with the corresponding ligands (major histocompatibility complex class I chain-related protein A/B, MICA/B) on the surface of tumor cells. Malignant tumors of epithelial origin usually highly express NKG2D ligands such as MICA, which can attract NK cells to kill tumor cells and also serve as an important basis for NK cell-based immunotherapy. Tumor cells highly express hypoxia-inducible factor-1α (HIF-1α), which promotes the expression of matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinases (ADAMs). These metalloproteinases hydrolyze MICA and other ligands on the surface of tumor cells to generate soluble molecules. These soluble ligands, when binding to NKG2D, cannot activate NK cells and also block the binding of NKG2D to MICA on the surface of tumor cells, enabling tumor cells to evade the killing effect of NK cells. Almost all organs in the digestive system originate from epithelial tissue, so the soluble ligands generated by the HIF-1α/MMPs or HIF-1α/ADAMs signaling pathways play a crucial role in evading NK cell killing. A comprehensive understanding of this immune escape process is helpful for a deeper understanding of the molecular mechanism of NK cell anti-tumor activity. This article reviews the molecular mechanisms of common digestive system malignancies evading NK cell killing, providing new insights into the mechanism of tumor immune escape.